GENETIC COMPLEXITY AND CONTEXT SPECIFICITY OF TRAITS IMPROVING WHEAT YIELD UNDER DROUGHT CONDITIONS - V. A. Krupnov (Вавиловский журнал генетики и селекции)
Under drought conditions, water shortage of varying duration and intensity is often combined with heat and other stresses, and years with favorable moisture are occasional. In these contrasting conditions, the key role in grain yield is played by growth habit, growing period, and technology. For example, in the late twentieth century temperate winters in the Volga region of Russia and improved technology allowed winter wheat to supplant spring wheat almost everywhere in the region. Identification and labeling of QTL has opened up new opportunities for identifying genetic differences between genotypes for each trait underlying traditional breeding, obtaining more information on parents to choose a pair of crosses, and performing selection. However, the effect of QTL, typically depends mainly on the genetic background (pleiotropy, epistasis, and use of alien genes), environment (time and intensity of drought, growth technology) and interaction between alleles and the environment. These factors demand that in each breeding cycle each new recombinant genotype be subjected to genetic identification together with accurate phenotyping. With resource-limited funding of breeding, the greatest benefit from the use of DNA technology can only be expected when working on populations, derived from crosses between of elite varieties and promising lines, and when traits cannot be improved solely by traditional phenotyping, not supplemented by genotyping.